Penanaman Kesadaran Lingkungan Melalui Alat Permainan Edukatif (APE) pada Taman Kanak-Kanak Kabupaten Aceh Besar - Sari, Cut Maya Aprita; Fadlia, Faradilla; Sentia, Prima Denny; Asmadi, Didi; Riza, Medyan; Hidayaturrahmi, Hidayaturrahmi (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
The regency of Aceh Besar often experiences environmental issues. Environmental awareness has become a serious matter that needs to be cultivated through character education from an early age through the learning process. Based on this, this community service initiative collaborates with 5 Kindergartens (TK) in Aceh Besar using a observational study. In this regard, the partner's problem lies in the lack of representative learning media to develop environmental awareness in children. This community service aims to educate children about the value of environmental awareness, which will affect their present and future social lives. Therefore, this community service project designs, produces, and distributes educational products through Educational Play Tools (EPT), such as flashcards and coloring books, as media for environmental awareness education.